The Concept of Antihero Represented by John Wick in Movie “John Wick Chapter 4” by Chad Stahelski - Kuspiyah, Hastuti Retno; Pratama, Deo; Agustina, Eka (Procedia of Social Sciences and Humanities, 2024)
The purpose of this study is to find out how many is type of the concept of antihero represented by John Wick in Movie “John Wick Chapter 4” by Chad Stahelski. The theory to analyse is from John F Rauthmann that causes three darks human trait, they are Narcissists, Machiavellians, Psychopaths. Moreover, this study focused on analyzing these three aspect of Antihero shown by John Wick they are Narcissists, Machiavellians, Psychopaths. Based on the results of data analysis found there are 41 data. They are the Narcissist (NRC) is 14 data (34%), Machiavellians (MCH) with a total of 16 data (39%), and Psychopaths (PSP) with a total of 11 data (27%). Therefore, it can be concluded that many uses of by the type of the concept of antihero represented by John Wick with a total of 41 data findings and the most dominant use is Machiavellians (MCH) with 16 data (39 %).